Subtle Cognitive Impairments in Patients with Long-Term Cure of Cushing’s Disease - Tiemensma, Jitske; Kokshoorn, Nieke E.; Biermasz, Nienke R.; Keijser, Bart-Jan S. A.; Wassenaar, Moniek J. E.; Middelkoop, Huub A. M.; Pereira, Alberto M.; Romijn, Johannes A. (The journal of clinical endocrinology and metabolism, 2010)
Context and Objective: Active Cushing’s disease is associated with cognitive impairments. We hypothesized that previous hypercortisolism in patients with Cushing’s disease results in irreversible impairments in cognitive functioning. Therefore, our aim was to assess cognitive functioning after long-term cure of Cushing’s disease. Design: Cognitive assessment consisted of 11 tests, which evaluated global cognitive functioning, memory, and executive functioning. Patients and Control Subjects: We included 74 patients cured of Cushing’s disease and 74 controls matched for age, gender, and education. Furthermore, we included 54 patients previously treated for nonfunctioning pituitary macroadenomas (NFMA) and 54 controls matched for age, gender, and education. Results: Compared with NFMA patients, patients cured from Cushing’s disease had lower scores on the Mini Mental State Examination (P = 0.001), and on the memory quotient of the Wechsler Memory Scale (P = 0.050). Furthermore, patients cured from Cushing’s disease tended to recall fewer words on the imprinting (P = 0.013), immediate recall (P = 0.012), and delayed recall (P = 0.003) trials of the Verbal Learning Test of Rey. On the Rey Complex Figure Test, patients cured from Cushing’s disease had lower scores on both trials (P = 0.002 and P = 0.007) compared with NFMA patients. Patients cured from Cushing’s disease also made fewer correct substitutions on the Letter-Digit Substitution Test (P = 0.039) and came up with fewer correct patterns on the Figure Fluency Test (P = 0.003) compared with treated NFMA patients. Conclusions: Cognitive function, reflecting memory and executive functions, is impaired in patients despite long-term cure of Cushing’s disease. These observations indicate irreversible effects of previous hypercortisolism on cognitive function and, thus, on the central nervous system. These observations may also be of relevance for patients treated with high-dose exogenous glucocorticoids.Cognitive function, reflecting memory, and executive functions are impaired in patients despite long-term cure of Cushing’s disease.